The Meaningful Fractal Fuzzy Dimension Applied to the Design of Self Organizing Maps - Peres, Sarajane M. [UNESP]; Netto, Marcio L. de A. (IEEE, 2008)
This paper presents the principal results of a detailed study about the use of the Meaningful Fractal Fuzzy Dimension measure in the problem in determining adequately the topological dimension of output space of a Self-Organizing Map. This fractal measure is conceived by combining the Fractals Theory and Fuzzy Approximate Reasoning. In this work this measure was applied on the dataset in order to obtain a priori knowledge, which is used to support the decision making about the SOM output space design. Several maps were designed with this approach and their evaluations are discussed here.